Optimalisasi Praktik Keperawatan Melalui Kerangka Theory of Planned Behaviour - Shinta Restu Wibawa; Agung Waluyo; Tuti Nuraini; Haeril Amir (Window of Nursing Journal, 2025)
Cancer patients often experience a variety of signs and symptoms that can significantly impact their quality of life. This research aims to apply the Theory of Planned Behavior to nursing care for cancer patients. This approach emphasizes the importance of attitudes, subjective norms, and perceived behavioral control in forming nursing diagnoses. n the context of cancer patients, understanding the factors of the Theory of Planned Behavior, namely attitudes toward the behavior, subjective norms, and perceived behavioral control, can help identify effective interventions to improve medication adherence, the adoption of a healthy lifestyle, and participation in follow-up care. This framework can increase understanding and improve patient care. The research method used is a case study approach. The research results show that the application of the Theory of Planned Behavior allows nurses to provide holistic care involving various aspects of cancer patients' lives including physical, emotional, social, spiritual and cultural. By understanding the concept of the Theory of Planned Behavior, nurses can recognize that changing a patient's behavioral habits requires planning, where from an accepting attitude to becoming a habit of carrying out therapy requires a process and needs support from both family and health workers so that goals and outcomes can be achieved.